DIALECTALITY OF INDONESIAN IN MERAUKE: PHONOLOGICAL, LEXICAL, AND PRAGMATIC VARIATIONS IN A MULTILINGUAL CONTEXT - Rawuh Yuda Yuwana (Acceleration: Multidisciplinary Research Journal, 2025)
This study examines the dialectal characteristics of Indonesian as spoken in Merauke, South Papua, a linguistically diverse region shaped by intense multilingual contact. While previous research has focused primarily on Papuan Malay and major urban varieties, Indonesian usage in Merauke remains under-documented. Using qualitative analysis of naturalistic spoken interactions, this study investigates phonological variation, lexical integration, and pragmatic patterns emerging from contact between Indonesian, indigenous Papuan languages, and migrant speech varieties. The findings reveal systematic phonological adaptations, including vowel lengthening and consonant simplification influenced by substrate languages; extensive lexical hybridization reflecting ecological and sociocultural realities; and pragmatic practices characterized by relational orientation, indirectness, and collectivist stance markers. Rather than representing deviations from standard Indonesian, these features form a stable regional variety shaped by sociocultural interaction. This study contributes empirical data to Indonesian dialectology and highlights the importance of integrating linguistic structure with cultural context in analyzing contact-induced language variation.